Analisis Potensi Pemanfaatan Sampah Anorganik Menjadi Energi Listrik Di TPA Kecamatan Tualang: Analysis Of Potential Utilization Of Anorganic Waste Into Electricity Energy At TPA District Tualang - Setiawan, Irfan Ricky (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2022)
Garbage is a major problem faced by the community in a, especially the community in Tualang District which experiences an increase in the amount of waste every year. Especially inorganic waste, inorganic waste in Tualang District is not managed properly, resulting in accumulation of inorganic waste volume in Tualang District TPA. Inorganic waste has great potential if it is converted into electrical energy by means of an incinerator. The purpose of this study is to calculate the potential of inorganic waste into electrical energy and the potential of electrical energy generated from the Waste Power Plant (PLTSa) and can help increase the amount of electrical energy supply. In this study using the incinerator method. From the calculation results, the amount of inorganic waste is 17.03 tons/day. The potential of electrical energy that can be generated is 14,762.21 kW or equivalent to 14 MW and in a year it can produce electrical energy of 129,316,966 kWh/year.